2005
DOI: 10.1172/jci200522656
|View full text |Cite
|
Sign up to set email alerts
|

A protective role for the A1 adenosine receptor in adenosine-dependent pulmonary injury

Abstract: Adenosine is a signaling nucleoside that has been implicated in the regulation of asthma and chronic obstructive pulmonary disease. Adenosine signaling can serve both pro-and anti-inflammatory functions in tissues and cells. In this study we examined the contribution of A 1 adenosine receptor (A 1 AR) signaling to the pulmonary inflammation and injury seen in adenosine deaminase-deficient (ADA-deficient) mice, which exhibit elevated adenosine levels. Experiments revealed that transcript levels for the A 1 AR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 46 publications
0
65
2
Order By: Relevance
“…72 By contrast, the adenosine A 1 receptor appears to play a protective role in adenosine-dependent pulmonary injury. 61 Thus, in the absence of A 1 receptors increased adenosine causes much more infiltration with eosinophils, neutrophils and lymphocytes. Furthermore, adenosine A 1 receptors were upregulated in the ADA-deficient lung; there were also changes in the other adenosine receptors.…”
Section: Some Examplesmentioning
confidence: 98%
See 2 more Smart Citations
“…72 By contrast, the adenosine A 1 receptor appears to play a protective role in adenosine-dependent pulmonary injury. 61 Thus, in the absence of A 1 receptors increased adenosine causes much more infiltration with eosinophils, neutrophils and lymphocytes. Furthermore, adenosine A 1 receptors were upregulated in the ADA-deficient lung; there were also changes in the other adenosine receptors.…”
Section: Some Examplesmentioning
confidence: 98%
“…However, two in vivo studies using A 1 k-o mice have provided evidence that A 1 receptors, probably on macrophages, play a protective role in inflammation. 60,61 Dendritic cells. The dendritic cells are antigen-presenting cells that function to activate T cells.…”
Section: Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine, acting at its receptors, promotes granulation tissue formation both directly and indirectly [14][15][16]. It has been shown that A 1 R and A 2A R hasten the resolution of acute inflammation by a variety of mechanisms [17][18][19]. All four adenosine receptor subtypes have also been implicated in revascularization although the A 2A R and A 2B R play the dominant roles in fibrosis.…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
“…If adenosine deaminase is only partially knocked out, the mice accumulate adenosine slowly over time, and develop a progressive lung fibrosis with increased myofibroblasts and collagen deposition, presumably by overstimulation of the profibrotic A2bR (36,37). In these models, it is unclear which of the adenosine receptors are the culprits, although adenosine deaminase/ A1 double-knockout mice have increased inflammation (38). In addition, IL-13 transgenic mice, which have increased A1, A2b, and A3, but not the anti-inflammatory A2aR, have recently been shown to have high levels of lung adenosine and increased lung inflammation (39).…”
Section: Discussionmentioning
confidence: 99%